Pressure‐Induced Metallic Conductivity in the Single‐Component Molecular Crystal [Ni(dmit)2]. Issue 24 (6th March 2014) - Cui, Hengbo; Tsumuraya, Takao; Miyazaki, Tsuyoshi; Okano, Yoshinori; Kato, Reizo
Abstract: Given that a molecular system has a soft lattice, high‐pressure applications are effective ways to discover new single‐component molecular metals and superconductors. In this study, we measured the high‐pressure electrical resistivity of a single‐component molecule crystal of [Ni(dmit)2 ] (dmit = 1, 3‐dithiole‐2‐thione‐4, 5‐dithiolate) up to 25.5 GPa by using a newly developed diamond anvil cell technique that generates high‐quality hydrostatic pressures. We successfully observed the metallic state over a wide temperature range above 15.9 GPa. Two different band calculation methods, tight‐binding calculations coupled with the interatomic repulsion model and ab initio DFT calculations, indicated that 2D and 3D Fermi surfaces appear under high pressures. Abstract : Four‐probe electrical resistivity measurements on the single‐component molecular crystal [Ni(dmit)2 ] (dmit = 1, 3‐dithiole‐2‐thione‐4, 5‐dithiolate) up to 25.5 GPa by using a diamond anvil cell (DAC) technique with high‐quality hydrostatic conditions reveal a metallic state above 15.9 GPa. Ab initio DFT calculations and tight‐binding band calculations indicate a 3D Fermi surface under high pressure, which explains the metallic state.